Strategi Kepala Madrasah dalam Mengembangkan Madrasah Go-Digital di Man Kota Batu - Pratama, Raka Wahyu; Suyeno; Langgeng Rachmatullah Putra3 (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The digital era has become one of the challenges for the world of education. This is because almost all life is related to digital, so education, including teachers and students, must also be able to make good use of digital. Likewise with schools, where with digital schools will be more visible so that teachers and students will also develop. This is where the research on the importance of madrasas that go digital lies. The research method used is qualitative. The results obtained include: 1) The digital-based MAN Batu departs from three things, namely orientation to modern educators and students, the quality of education in accordance with the times, and the community's appreciation and expectations for madrasah graduates, especially in MAN Batu. 2) The principal's strategy for madrasas has three important things, including: first, having a reference source for schools and digital madrasas. In this case, what is the focus is the introduction and examples of modern schools that have currently made improvements and developments to the digital world. So that MAN Batu emulates them, including domestic and foreign. Second, human resource management related to learning, in this case 1 semester 1 application training is carried out with the aim that teachers can understand well related to the application so that it can be used. These applications are for example Flipbook, Macro Media, E-learning etc. Third, the management of facilities and infrastructure in madrasas. This is indeed the priority is that the physical facilities after that will be carried out to digital facilities. Where the development includes digital libraries, digital laboratories, digital learning, websites and also correspondence that can be done digitally or online.